Komunikowanie w rodzinie w sytuacji zapewnienia opieki osobie po udarze mózgu - Koc-Kozłowiec, Barbara (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Stroke is the second cause of death in people over 60 years old. It is estimated that approximately 70% of patients who survive a stroke becomes disabled. Everyday activities (walking, dressing and eating) become unenforceable, the patient needs the care of others. The disease – stroke – a crisis for the family. This applies especially to families in which the husband/wife is an older person and the adult children have their own families. In this work the author presents communication of families in situation to provide care for the sick at home.
Keywords: communication; crisis in family; family; stroke